PENGARUH AROMATERAPI LEMON TERHADAP PENURUNAN RASA NYERI PADA IBU POST PARTUM SECTIO CAESAREA - Yuliani, Eka; Aksari, Septi Tri; Khomsah, Yuli Sya’baniah; Rantauni, Dahlia Arief (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
The puerperium or post partum period is the period after childbirth is completed up to 6 weeks or 42 days. After the postpartum period, the reproductive organs will slowly undergo changes as before pregnancy. Sectio Caesarea surgery method can have several impacts, the most common of which is pain. Lemon aromatherapy is a type of non-pharmacological therapy of high concentrations of essential oils obtained from plants that can be massaged, inhaled, or mixed into bath water in pure form.The subject in this study was Mrs. N P1A0 aged 28 years with complaints of pain in the postoperative wound. Data sources and types of data used use primary and secondary data. From the results of the study of giving lemon aromatherapy to postoperative patients, it was found that there were changes in pain between before and after giving lemon aromatherapy using diffueser. Lemon aromatherapy is a type of aromatherapy that is used to treat pain and anxiety. After administering lemon aromatherapy for 2 days in this case, the results showed a decrease in postoperative pain. In this case, the patient's pain scale was reduced from 5 moderate pain intensity to 3, mild pain intensity